136-68: Response to cardiac resynchronization therapy with quadripolar lead - preliminary results of ResQ-CRT prospective study. (10th June 2016) - Menardi, Endrj; Giammaria, Massimo; Notarstefano, Pasquale; Mazza, Antonio; Giovannini, Tiziana; Senatore, Gaetano; Giuggia, Marco; Zacà, Valerio; Rametta, Francesco; Pizzetti, Fabrizio; Vado, Antonello
Abstract: Purpose: In CRT, left ventricle (LV) quadripolar leads offer the chance to overcome implant difficulties (phrenic nerve stimulation (PNS), unsatisfactory thresholds or pacing site) and potentially to reduce the need for reoperation, but few prospective data are available about effects on patient's response. This study aims to observe the evolution of CRT-D with quadripolar LV lead in terms of electrical parameters and patient's outcome, observing the differences between Responders and Non-Responders. Method: Were prospectively observed, in 15 Italian hospitals, 152 patients [(Average ± SD): Age(y) 69.4 ± 9; 76.3% Man; 42% Ischemic; 68% NYHA III; LV EF(%) 27.6 ± 5.5] in which the CRT-D device was programmed with LV pacing from one of distal dipoles, when possible (142 distal, 93%). After 4 ÷ 7 (6M Follow-Up (FU)) and 10 ÷ 14 (12M FU) months the patient clinical outcome is evaluated and the LV lead programming is recorded. Definition of Responder: improvement of HF Clinical Composite Index (CCI improved = no major clinical events and NYHA + health state improved) and at least one between improvement of LV Ejection Fraction (EF) more than 5 percentage points and 10% reduction of the LV End Systolic Volume (ESV), measured with echocardiograph. Summary: Were analyzed 117 "6M FUs"; 35 patients (30%) were classified as Non-Responder (NR), 8 (23% of NR) only due to echocardiographic parameters not improved, while 12 patients (34% of NR) had echocardiographic parameters improved but CCI not improved. It was noticed an average increase in LV EF (+9 percentage points [95% C.I. 8 ÷ 10], p < 0.001) from baseline in all patients; in NR patients the mean increase of EF was less than 5 percentage points (p < 0.001). Reduction of the LVESV from baseline was significant for all patients and in particular in Responder group (average LVESV reduction = 27.7 %, N = 60, [95% C.I. 21.1 ÷ 34.4], p < 0.001), but not in NR group (average 7.5 %, N = 26, [95% C.I. -3.2 ÷ 18.1], p = 0.08). At 6M FU, in 21 NR patients (60% of NR) the LV configuration was changed from distal to proximal dipoles, while it was not possible, for high threshold or PNS, in 5 patients (14%). Otherwise it was considered not clinically relevant. Were also preliminarily analyzed 81 "12M FUs"; of 26 patients (32%), classified as NR at 6M FU, 15 of them had the LV configuration changed from distal to proximal dipoles at 6M FU; 8 (53%) of these patients were classified as Responder at 12M FU. The other 11 patients, also classified as NR but with no LV configuration change at 6M FU, became Responder at 12M FU in 4 cases (2 of 8 with LV distal; 2 of 3 with LV proximal). Conclusion: Data indicate a rate of Non-Responder with LV stimulation on distal dipoles as expected from previous studies. Follow-up data at 12 months, though preliminary, show potential benefit of quadripolar lead availability on this population.